THE UNIQUENESS OF ABDIKAYUM YULDOSHEV'S STORYTELLING - Avezova Gulnora Samandarovna (Zeta Repository, 2023)
Human spirituality has always been a leading theme. In particular, the main goal of creative people is the idea in their works, which is often similar, that is, the spirituality of a person, to raise it, to awaken feelings of hatred for evil and love for goodness in hearts. But in the infinite universe, there is no phenomenon that is completely similar to each other. The work of art and the image of the characters in it is an artistic expression of this diversity and originality. This article discusses the storytelling of Abduqayum Yuldoshev.